Microscopic examination of internal parasites in Iraqi camels (Camelus dromedarius) with molecular focus on Trichostrongylus spp - Albayati, H. H.; Al Khafaji, A. M.; Al-Karagoly, H.; Kamel, A. (Helminthologia, 2024)
The camel has played a role in human civilization since its inception and holds significant importance in the customs and agricultural practices of various nations. This study examined the prevalence of internal parasitic infestations in camels within the Al-Diwaniyah and Al-Najaf provinces of Iraq from December 2021 to September 2022. A total of 200 fecal samples were randomly collected from farm camels, revealing that these animals were affected by one or more types of intestinal parasites. exhibited the highest prevalence at 56 %, followed by at 28.5 %, at 14.5 %, and at 1 %. Among these parasites, . had the highest percentage at 33 %, followed by (12.5 %), (10.5 %), . (8 %), . (7 %), . (6 %), and . (6 %). Furthermore, mixed-species or single-species infections in camels were observed, including (4 %), . (3.5 %), . (3 %), (2.5 %), . (2 %), and (1 %). Additionally, nested PCR was employed to identify ., with 45.4 % of camels testing positive for this particular parasite.